Flower Bath: A Preliminary Research on Its Practice and Function in Malay Society (Melayu: Jurnal Antarabangsa Dunia Melayu, 2023)
This paper discusses the flower bath as a practice and its function in Malay society. Bathing with certain flowers is a cultural tradition in Malaysia, Indonesia, Singapore, Thailand and other related countries. This study aims to provide a clear understanding of flower bath, including its practice and function in Malay society. This study uses the interview method with a traditional medicine practitioner who has been and still upholds the custom of flower bath in Parit Haji Amin, Sungai Rawa, Parit Buntar. This method was carried out in January 2021 to obtain primary sources and justification for the selection based on her experience of being involved in traditional medicine for 30 years and remains active in traditional medicine work. The results found that flower bath involves various types of flowers, along with its preparation method and the purpose of its implementation. Moreover, it is found that flower bath has animism, dynamism and Hindu and Buddhist beliefs concerning the spirit and soul. The practice of flower bath has various purposes, such as enhancing a bride’s glow, dispelling bad luck and obtaining a wish, such as obtaining black magic, position, allure and wearing charm needles (susuk). However, this practice of flower bath is no longer popular in the Malay community because most of them have changed to commercial flower bath. In addition, the tradition of flower bath practiced by the Malay community highly contradicts Islamic teachings because there is an element of believing in spirits, which can lead to polytheism.Full text: PDF